Strategi Branding Guna Meningkatkan Kesadaran Kesehatan Mental: Pendekatan Inovatif Pada Industri Perawatan Kulit (Skincare) Pada Merek Adara Cosmetics. - Harini, Rizka; IGM Wirabrata; Widyastuti, Sri (PendIPA Journal of Science Education, 2025)
This study aims to explore how brand X can integrate mental health awareness into its branding strategies to enhance brand equity. The methodology employed in this study is a mixed-method approach, incorporating both surveys (quantitative) and interviews (qualitative). Surveys were conducted with 191 respondents who use brand X products to measure the relationship between mental health awareness and various elements of brand equity. Additionally, in-depth interviews were conducted with the management of brand X to gain insights into the branding strategies being implemented. The findings reveal a significant positive relationship between mental health awareness and all elements of brand equity, including brand awareness, brand association, perceived quality, and brand loyalty. Mental health awareness correlates at 52.8%, contributing to increased brand recognition and positive associations, as well as enhancing the perceived quality of the products. Consumers who perceive brand X as caring about their mental health tend to demonstrate greater loyalty to the brand. In conclusion, integrating mental health awareness into branding strategies not only positively impacts brand equity but also strengthens the emotional connection between consumers and the brand. Therefore, it is recommended that brand X continues to develop campaigns focused on mental health and strengthens collaborations with mental health professionals to enhance awareness and education in society.